THE INFLUENCE OF ISLAMIC BANKING KNOWLEDGE AND JOB OPPORTUNITY PERCEPTIONS ON CAREER INTEREST IN ISLAMIC BANKING (A Case Study Of Islamic Banking Students At Universitas Islam Malang) - Boyratan, Neha Nurul Aisyah; Mawardi, M. Cholid; Hardaningtyas, Ratna Tri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the influence of Islamic banking knowledge and job opportunity perception on students’ career interest in Islamic banking. The research was conducted among active students of the Islamic Banking Study Program at the Islamic University of Malang, using a correlational quantitative approach. The sampling technique used was purposive sampling, involving 106 respondents who had taken courses related to Islamic banking. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS software. The results show that both Islamic banking knowledge and job opportunity perception have a positive and significant effect on career interest in Islamic banking, both simultaneously and partially. These findings indicate that enhancing students’ understanding of Islamic banking principles and practices, along with their perception of promising career prospects in the industry, can encourage their interest in pursuing careers in this sector.